Cloning of the human alpha 1 antichymotrypsin gene and genetic analysis of the gene in relation to alpha 1 antitrypsin deficiency. Issue 6 (June 1988) - Kelsey, G D; Abeliovich, D; McMahon, C J; Whitehouse, D; Corney, G; Povey, S; Hopkinson, D A; Wolfe, J; Mieli-Vergani, G; Mowat, A P
Abstract : Deficiency of alpha 1 antitrypsin (Pi) is clinically heterogeneous and the unpredictability of the clinical manifestation in a person of phenotype PiZ, which may vary from severe childhood liver disease to normal health, is a problem in genetic counselling. This problem may increase as couples at risk who have not had an affected child are identified in screening programmes. One possibility is that genetic variation of other protease inhibitors may influence the prognosis. With this in mind we report the isolation of the human gene for alpha 1 antichymotrypsin (AACT) on a series of cosmid clones, with restriction mapping of about 70 kb around the gene. A probe pACE3.4 derived from the 5' end of the gene defines sequences which have been assigned to chromosome 14 using somatic cell hybrids and has been used to show a common TaqI polymorphism with allele frequencies of AACT6 = 0.7 and AACT3 = 0.3 in Europeans. pACE3.4 is closely linked to alpha 1 antitrypsin (maximum lod score in males +2.29 at theta = 0; in females Z = +6.11 at theta = 0.032). Analysis of Pi-AACT haplotypes in 31 families ascertained through PiZ or PiSZ subjects did not show any linkage disequilibrium. The distribution of AACT6 and AACT3 alleles in 16 unrelated PiZ patients presenting with childhood liver disease and five unrelated PiZ patients with adult chest disease did not differ significantly from each other. These results suggest that if genetic variation at the AACT locus does influence the outcome of alpha 1 antitrypsin deficiency, such variation is not in linkage disequilibrium with the AACT polymorphism reported here.